DUKUNGAN DAN HAMBATAN DALAM PELAKSANAAN PRAKTIK PERAWATAN KESEHATAN MASYARAKAT (PERKESMAS): A SYSTEMATIC REVIEW - Tafwidhah, Yuyun; Putri, Triyana Harlia (LPPM Universitas Harapan Bangsa, 2023)
Public health care (perkesmas) is one of the activities organized by puskesmas to improve the degree of public health and as an effort to increase the reach of health services and program coverage. Perkesmas needs to pay attention to support and obstacles to determine the right strategy for its management. The purpose of this systematic review is to determine the support and obstacles in the implementation of perkesmas. The literature search method is carried out on the PubMed, Science Direct, and Mendeley databases published in 2019 – 2023, the results of original research and articles can be accessed in full text. The keywords used in the search were 'community nurses', 'community nursing', and 'community nursing management'. The results show the required nurse competence not only in nursing but also in non-nursing. Management support is carried out to improve inter- and interprofessional cooperation. Barriers encountered include poverty, homelessness, poor health literacy, language, limited access to health services to lack of stakeholder attention. Conclusions in the management of perkesmas can pay attention to the support and obstacles identified.